In-contest body acceleration profiles for the judo male and female weight divisions - Santos, L.; Federolf, P. A.; Schneider, F.; Pocecco, E.; Fernández-Río, J.; Iglesias-Soler, E.; Carballeira-Fernández, E.; Uriarte, S.; Dopico-Calvo, X. (Frontiers in Sports and Active Living, 2024)
Introduction: This study aimed to determine the body accelerations (BA) profile of the judo contest of the male and female weight divisions and to ascertain the involvement of the vertical, mediolateral and anteroposterior axes in it.